2011
DOI: 10.1093/jpepsy/jsr053
|View full text |Cite
|
Sign up to set email alerts
|

High Peer Popularity Longitudinally Predicts Adolescent Health Risk Behavior, or Does It?: An Examination of Linear and Quadratic Associations

Abstract: New theoretical models can be useful for understanding the complex manner in which health risk behaviors may be reinforced within the peer context.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
44
0
8

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 21 publications
3
44
0
8
Order By: Relevance
“…Most studies that studied the associations between popularity and adjustment outcomes in a similar age group mainly examined how popularity predicted several outcome behaviors instead of the reverse (e.g., Prinstein et al 2011). However, used a cross-panel design and showed that popularity predicted greater engagement in risk behavior, but also that smoking predicted increased popularity 2 years later.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies that studied the associations between popularity and adjustment outcomes in a similar age group mainly examined how popularity predicted several outcome behaviors instead of the reverse (e.g., Prinstein et al 2011). However, used a cross-panel design and showed that popularity predicted greater engagement in risk behavior, but also that smoking predicted increased popularity 2 years later.…”
Section: Discussionmentioning
confidence: 99%
“…Adolescents' popularity in the peer group is associated with various negative as well as positive behaviors, such as smoking tobacco, drinking alcohol, and being cooperative (e.g., Prinstein et al 2011;Prinstein et al 2003). Popularity is typically measured using peer reports, with an individual's popularity being determined by the standardized difference between the number of ''most popular'' and ''least popular'' nominations received by members of a reference group (e.g., classmates).…”
Section: Introductionmentioning
confidence: 99%
“…Adolescents' popularity is positively associated with drinking alcohol (Mayeux, Sandstrom, & Cillessen, 2008), smoking tobacco (Prinstein, ChoukasBradley, Helms, Brechwald, & Rancourt, 2011) and smoking cannabis (Prinstein et al, 2011). Sexual intercourse, which in adolescence is seen as a risk behaviour because of related unintentional pregnancy and transmission of sexually transmitted diseases (Saewyc, Magee, & Pettingell, 2004), is also positively associated with popularity (Hawke & Rieger, 2013;Mayeux et al, 2008;Prinstein et al, 2011;Prinstein, Meade, & Cohen, 2003).…”
mentioning
confidence: 99%
“…Sexual intercourse, which in adolescence is seen as a risk behaviour because of related unintentional pregnancy and transmission of sexually transmitted diseases (Saewyc, Magee, & Pettingell, 2004), is also positively associated with popularity (Hawke & Rieger, 2013;Mayeux et al, 2008;Prinstein et al, 2011;Prinstein, Meade, & Cohen, 2003). However, studies that also took likeability into account showed that alcohol use was not associated with likeability (Mayeux et al, 2008), nor was sexual intercourse (Hawke & Rieger, 2013).…”
mentioning
confidence: 99%
See 1 more Smart Citation